Use of Bronchoalveolar Lavage To Detect Galactomannan for Diagnosis of Pulmonary Aspergillosis among Nonimmunocompromised Hosts - Nguyen, M. Hong (American Society for Microbiology, 2007)
Pulmonary aspergillosis in nonimmunocompromised hosts, although rare, is being increasingly recognized. The diagnosis of pulmonary aspergillosis is difficult, since the recovery of Aspergillus from respiratory samples cannot differentiate colonization from invasion. We assessed the role of bronchoalveolar lavage (BAL) in detecting galactomannan (GM) for diagnosing pulmonary aspergillosis in 73 nonimmunocompromised patients with pulmonary infiltrates for whom the test was ordered. Six patients had pulmonary aspergillosis, two each with acute invasive pulmonary aspergillosis, chronic necrotizing pulmonary aspergillosis, and aspergilloma. All six patients had a BAL GM level of ≥1.18. The sensitivity, specificity, and negative predictive value (NPV) for a BAL GM level of ≥1.0 were 100%, 88.1%, and 100%, respectively. Notably, the positive predictive value (PPV) was only 42.9%, likely reflecting the low prevalence of pulmonary aspergillosis among nonimmunosuppressed patients. The combination of BAL microscopy and culture had a sensitivity and NPV similar to those of BAL GM detection but a higher specificity and PPV (92.5% and 54.6%, respectively). Moreover, a BAL GM test did not identify any cases that were not diagnosed by conventional methods like microscopy and culture. In conclusion, there was no conclusive benefit of determining BAL GM levels in the diagnosis of pulmonary aspergillosis among nonimmunocompromised hosts. Given the likelihood of false-positive results, a BAL GM test should not be ordered routinely in this population.